Implementation Audit Internal of Quality Management System Iso 9001:2015 in the Purchasing Activities Technical Department at Pt Sango Indonesia - Rilla Gantino; Evi Lutfiyana (Ridwan Institute, 2023)
PT Dunia Express Transindo is a